VafusQ: A methodology to build visual analysis applications with data quality features. (October 2019) - Triana, Jhon Alejandro; Zeckzer, Dirk; Hagen, Hans; Hernandez, Jose Tiberio
The use of interactive applications to support the decision-making process is more common every day. However, a huge amount of data is required in order to make more informed decisions. Fortunately, with the arrival of new technologies there are many data sources available. This requirement of data causes heterogeneity and data quality problems. A set of data quality problems are reduced in the preprocessing stage. However, many data quality issues persist after the preprocessing stage. For this reason, we proposed a methodology to take the data quality problems, to represent them and simultaneously support the analysis process. In addition, an application is developed as a use case of the methodology by analyzing the public transport system in Bogotá. Furthermore, a case study is performed to test the usefulness of the developed application. As a result, the methodology made possible the development of interactive visualizations that constitute an application that is useful to achieve the analysis tasks by including data quality features.